Actualization of Principal Instructional Leadership in the Implementation of Differentiated Learning to Realize Students’ Well-Being - Hariyati, Nunuk; Riyanto, Yatim; Sujarwanto, Sujarwanto; Suyatno, Suyatno; Islamiah, Nia (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to reveal the actualization of the principal’s instructional leadership in carrying out differentiated learning that embodies students’ well-being. The method used in this study was qualitative, with the design of multi-case studies through constant comparative analysis using Nvivo Software. The informants in this study were the principal, vice principal, teachers, learners, and parents of students. Subjects were taken purposively consisting of the principal, vice principal, teachers, students, and parents and measured by interviews, observation, and documentation analysis. The study’s findings revealed that the principal took several actions that reflected instructional leaders’ behavior. It included communicating school objectives about implementing differentiated learning in the classroom, supervising, and evaluating related to learning, monitoring student progress, developing teacher professional abilities, and demonstrating concern for teachers and students. From the results, this research is expected to (1) contribute to developing the concept of instructional leadership, which places student well-being as the primary orientation in the learning process, (2) can foster the initiation of school principals in building strategies to maximize and empower school resources in supporting the implementation of differentiated learning, (3) increase the actualization of the teacher’s role and function as a front of the liner in realizing differentiated learning in the classroom, and (4) build awareness about the importance students well-being for parents.